Analytical-function correction to the Hartmann–Tran profile for more reliable representation of the Dicke-narrowed molecular spectra. (February 2020) - Konefał, M.; Słowiński, M.; Zaborowski, M.; Ciuryło, R.; Lisak, D.; Wcisło, P.
Highlights: Introduction of an analytical-function correction to the frequency of the velocity-changing collision parameter in the Hartmann–Tran profile. The correction is called the β correction. The β HTP is an approximation of the partially correlated quadratic speed-dependent billiard-ball profile. The β correction is particularly important for the analysis of high-resolution spectra influenced by the Dicke narrowing. Abstract: The β -corrected Hartmann–Tran profile (HTP) constitutes an approximation of the partially correlated quadratic speed-dependent billiard-ball profile (SDBBP) easily applicable in calculations. We extend the approach originally developed for self-perturbed molecules [Wcisło et al. J. Quant. Spectrosc. Radiat. Transf. 177, 75–91 (2016)] to systems with a wide range of perturber-to-absorber mass ratios, including those relevant for atmospheric studies. This approach combines the computational simplicity of the HTP with the more physically justified rigid-sphere model for velocity-changing collisions. It is important for the analysis of high-resolution spectra influenced by the Dicke-narrowing effect. The β -corrected HTP enables high quality analytical representation of experimental spectra without incurring the high computational cost of more advanced line-shape models. This correction is directly applicable to any other line-shape model based on the hard-collision model for velocity-changing collisions.